2021
DOI: 10.1002/icd.2268
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the development of honesty in children through the domains‐of‐socialization approach

Abstract: Honesty is an important value that children acquire through socialization. To date, the socialization process by which children learn to behave honestly remains relatively unexamined.Researchers may have left this area of research relatively unexamined because there is no framework to understand how parents socialize honesty and lie-telling in their children.As such, we suggest that the domains-of-socialization approach, which organizes the socialization process into various domains based on different aspects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 111 publications
(214 reference statements)
1
7
0
Order By: Relevance
“…Influenced by Grusec and Davidov’s (2010) control domain of socialization theory, most studies focus on exploring how parental control affects children’s lying behavior. Theoretical accounts suggest that parental control may be associated with more lying behavior in children (Tong & Talwar, 2021), while other studies found that parental control reduces children’s lying negatively via theory-of-mind development (Ma et al, 2015) or is moderated by children’s inhibitory control (Talwar, Lavoie, et al, 2017). This study was inconsistent with previous studies as results showed that parental control did not play a role in children’s lying nor moderate the link between theory-of-mind and lying.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Influenced by Grusec and Davidov’s (2010) control domain of socialization theory, most studies focus on exploring how parental control affects children’s lying behavior. Theoretical accounts suggest that parental control may be associated with more lying behavior in children (Tong & Talwar, 2021), while other studies found that parental control reduces children’s lying negatively via theory-of-mind development (Ma et al, 2015) or is moderated by children’s inhibitory control (Talwar, Lavoie, et al, 2017). This study was inconsistent with previous studies as results showed that parental control did not play a role in children’s lying nor moderate the link between theory-of-mind and lying.…”
Section: Discussionmentioning
confidence: 99%
“…As previously mentioned, children continue to undergo dramatic shifts in theory-of-mind understanding past 3 years of age (e.g., Wellman et al, 2001). While the development of more complex theory-of-mind skills (e.g., false belief understanding) equips children with sufficient theory-of-mind to tell a lie, better theory-of-mind may also help children to better internalize their parents’ socialization practices of forbidding them to lie (Tong & Talwar, 2021). As such, in this study, parenting practices may have affected 3- to 6-year-olds’ motivation to lie rather than just their ability to tell a lie, and the opposing effects of these two mechanisms may have canceled each other out.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the few existing studies on parenting in the literature have measured parenting styles (Popliger et al., 2011; Ma et al., 2015; Talwar et al., 2017; c.f. Dykstra et al., 2020), Tong and Talwar (2021) have argued that such a broad notion is not useful for deception development and that a domain‐specific approach would be more appropriate.…”
Section: Introductionmentioning
confidence: 99%
“…Parents are an essential agent in children’s developmental trajectories of lie-telling through their nurturing and socializing behaviors [ 34 ]. According to the domain of socialization framework proposed by Grusec and Davidov [ 35 ], socialization takes place across several domains and includes approaches such as guided learning, group participation, control, protection, and reciprocity, through which parents are contributing to their children’s socialization of honesty and to the development of socially accepted behaviors [ 34 , 36 , 37 ]. Guided learning and group participation can contribute to children’s ability to differentiate between truth and lies and choose accordingly.…”
Section: Introductionmentioning
confidence: 99%